CREATIVE PROCESS ANALYSIS OF CHUSIN SETIADIKARA IN CHUSIN'S REALISTIC PAINTING EXHIBITION, A THESIS - Evan Sapentri (Universitas Sebelas Maret, 2017)
Painting becomes one of the media expressions and self-expression of artists in conveying and embedding every artistic idea. The realist painting of Chusin Setiadikara artistically exhibited in the National Gallery of Indonesia, certainly can not be released with the involvement of technology in the creative process. The use of cameras when processing the painting is a manifestation of the existence of technology covered in artwork before it is poured into the canvas. This paper aims to see the creative process in creating a realist painting by Setiadikara, and connect it with the role of technology in the process of creation, and to see the subject of creativity that appears and presented in the painting. In answering the problem, literature study is used to support the wealth of data in order to observe and answer the existing phenomenon. The results of this study indicate that Chusin Setiadikara not only talks about the realism form embodied in his work. He also alludes to the form of creative work that manifests in every work of his work. Camera used as Chusin as a vehicle to pour ideas/conceptual ideas that poured into the painting. Not only do the realities work, he also presents a new form of reality in his paintings.